2017
DOI: 10.1115/1.4036268
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Drop Analysis of Pilot-Control Globe Valve With Different Structural Parameters

Abstract: Pilot-control globe valve (PCGV) can use the pressure drop caused by fluid flowing through the orifice located at valve core bottom to open or close the main valve using a small pilot valve. In this paper, computational fluid dynamics (CFD) method is adopted to analyze the pressure drop before and after valve core of PCGV and minor loss of orifice under different structural parameters and inlet velocities, and the simulation results show a good agreement with the experimental results. It turns out that the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Extensive CFD studies of valve flows have been conducted in support of understanding and improving designs. Some examples of such CFD studies can be found in [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Similar to experimental measurements, there are uncertainties/errors in all of the industrially practical CFD methods.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive CFD studies of valve flows have been conducted in support of understanding and improving designs. Some examples of such CFD studies can be found in [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Similar to experimental measurements, there are uncertainties/errors in all of the industrially practical CFD methods.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding equations are as follows: where ρ is the water vapor density, u is the water vapor velocity, p stands for pressure, μ stands for the dynamic viscosity of water vapor, C v and C p stand for specific heat, Pr stands for the Prandtl number, and τ ij stands for viscous stress. As for the realizable k-ε turbulence model, it has been described in our previous study [ 34 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Forder, Thew, and Harrison (1998) presented a numerical erosion model that could predict erosion rates, and they indicated that velocity was a major reason for erosion. Jin, Gao, Zhang, and Qian (2017) emphasized that inlet velocity has an important effect on pressure drop and determined the pressure distribution with variable inlet velocities. Liu, Zhao, and Qian (2017) analyzed the flow characteristics, such as water volume fraction, flow rate and turbulent intensity, and then obtained the effect of these factors on the flow features of fluid.…”
Section: Introductionmentioning
confidence: 99%